(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
The results of two-year studies on the influence of pre-sowing treatment and foliar fertilization with organic fertilizers, using different technologies for protecting plants from weeds (intensive or organic), on the diameter of baskets, yield and oil content of linoleum-type sunflower hybrids Zlatson and Guslyar are highlighted. An increase in the diameter of the baskets of the Guslyar hybrid by 0.6-1.1 cm was noted under intensive and organic technology when spraying plants in the phase of 3-4 pairs of leaves with the preparation Humisol and in the phase of 5-6 pairs of leaves with the preparations Lianum or Humisol. The highest yield of sunflower is formed under intensive cultivation technology - 1.29 t/ha, compared to organic technology - 1.03 t/ha. Spraying plants of the Guslyar hybrid with organic fertilizers Lianum or Humisol in the phase of 5-6 pairs of sunflower leaves helps to increase yield by 0.10-0.13 t/ha under intensive cultivation technology and by 0.10-0.11 t/ha under organic technology. A significant increase in sunflower oil content by 0.6-1.1% was noted under organic technology of growing sunflower hybrid Zlatson in the variants of pre-sowing seed treatment and spraying of plants in the phase of 3-4 pairs of leaves with organic fertilizers Lianum and Humisol and spraying with the drug Lianum in the phase of 5-6 pairs of leaves, as well as the hybrid Guslyar - by 0.9-1.2% in the variants of spraying of plants in the phase of 3-4 pairs of leaves with organic fertilizers Lianum and Humisol, compared to the control without the use of organic fertilizers. Therefore, to form a larger diameter of baskets and create more favorable conditions for the formation of higher yields of sunflower seeds, it is advisable to use intensive technology for protecting plants from weeds and spray plants with organic fertilizers Lianum or Humisol in the phase of 5-6 pairs of sunflower leaves. At the same time, organic cultivation technology (without herbicides) in the variants of using organic fertilizers Lianum or Humisol helps to increase the oil content of sunflower by 0.6-1.2%.